Anti-stress technologies in the prevention and correction of psychosomatic disorders of schoolchildren - Karmanova, Zh.A.; Autayeva, I.; Kasymova, L.S. (Karagandy University of the name of acad. E.A. Buketov, 2023)
This article discusses the current problem of the increase in the number of psychosomatic diseases in school-age children, representing a group of painful conditions that appear as a result of the interaction of mental and physiological factors. Drawing a parallel between a sharp increase in stress effects on school-age children with a simultaneous decrease in their adaptive capabilities and the development of psychosomatic disorders, the authors consider the problem of stress as an important component of the educational process of the school. The authors attempt to reveal the main methods of reducing stress levels in adolescents. As a result of the study, it is concluded that it is necessary for teachers to acquire skills in applying knowledge and skills to create methods of work of specialists of educational institutions aimed at stress-free teaching of schoolchildren taking into account the psychosomatic factor.
Keywords: psychosomatic disorder; stress; emotional stress; prevention of psychosomatic disorders; correction of psychosomatic disorders; educational process of the school